Evaluation of Bioactive Compounds and Antioxidative Activity of Fermented Green Tea Produced via One- and Two-Step Fermentation - Huiling Xu; Jong Hyoung Hong; Dabin Kim; Young Hun Jin; Alixander Mattay Pawluk; Jae-Hyung Mah (MDPI AG, 2022)
This study investigated the influence of one- and two-step fermentation on bioactive compound production in fermented green tea, i.e., one-step fermented green tea (OFG) and two-step fermented green tea (TFG). One-step fermentation entailed acetic acid fermentation, while two-step fermentation consisted of lactic acid fermentation followed by acetic acid fermentation. Acetobacter pasteurianus PCH 325, isolated from an over-ripened peach, was selected for acetic acid fermentation based on its growth and organic acid production characteristics. Acetic acid fermentation conditions were optimized for one- and two-step fermentation: 3% fermentation alcohol for both processes; 8% and 4% sucrose, respectively; and fermentation at 25 °C for both processes. For lactic acid fermentation of TFG, the inoculum and optimized conditions reported previously were used. Under the optimized conditions, the acetic acid content in OFG and TFG increased 21.20- and 29.51-fold, respectively. Furthermore, through two-step fermentation, γ-aminobutyric acid and lactic acid were produced up to 31.49 ± 1.17 mg/L and 243.44 ± 58.15 mg/L, respectively, which together with acetic acid could contribute to the higher DPPH scavenging activity of TFG. This study suggests that two-step fermentation may be a valuable strategy in industry for raising the amount of acetic acid and/or providing additional bioactive compounds.